Climatic Subjects (transcript Verlag, 2025)
Who, or what, is the contemporary climatic subject? Addressing the climate crisis in thought, imagination, and in action requires a connection between scholars, artists, journalists, and activists. The contributors to this volume put such a cooperation into practice and present not only academic articles, but also interviews, short stories, poems, and political essays. Readers will encounter the ›climatic subject‹ as an entity and as a historical force. But they will also hear the ›climatic subject‹ posed as a question, a displacement of subjectivation under the condition of the climate crisis. Finally, they will find the ›climatic subject‹ as a connector for new subjectivities yet to be embodied in cultural practice.